Preoperative Neutrophil-lymphocyte Ratio as a Predictor of Overall Survival in Patients with Localized Renal Cell Carcinoma - Widz, Damian; Mitura, Przemyslaw; Buraczynski, Pawel; Plaza, Pawel; Bar, Marek; Cabanek, Michal; Nowak, Grzegorz; Ostrowska, Anna; Bar, Krzysztof (Urology Journal, 2020)
Purpose: The neutrophil-to-lymphocyte ratio (NLR), as an indicator of the systemic inflammatory response, predicts adverse outcomes in many malignancies. We investigated its prognostic significance in patients with non-metastatic renal cell carcinoma. Materials and Methods: We retrospectively evaluated data of 196 consecutive non-metastatic RCC patients who underwent radical or partial nephrectomy between 2010 and 2012 at a single center. Overall survival (OS) was assessed using the Kaplan-Meier method and compared using the log-rank test. We applied univariate and multivariate Cox regression models to evaluate the prognostic value of dichotomized NLR for OS. Results: At a median follow up of 68 months, high NLR (? 2,69) correlated with worse survival outcome (P = .006 in log-rank test) and higher tumor stage (P = .035). Univariate and multivariate analysis identified elevated NLR (P = .039), as well as age (P = .002), high Fuhrmann grade (P = .002) and high pathologic T stage (P < .001), as significantly associated with overall survival. Conclusion: In our cohort, an elevated neutrophil-to-lymphocyte ratio is significantly associated with worse OS on univariate and multivariate analysis. Consequently, the NLR is an easily acquired biomarker, which may be useful in pretreatment patient risk stratification.